2022
DOI: 10.1155/2022/4452687
|View full text |Cite|
|
Sign up to set email alerts
|

A Signature of Genes Featuring FGF11 Revealed Aberrant Fibroblast Activation and Immune Infiltration Properties in Keloid Tissue

Abstract: Keloid is a fibroproliferative disorder in the skin, which manifested with extensive deposition of collagen and extracellular matrix. Its etiology remains a mystery and its recurrence rate remains high despite combinative treatment regimens. Current hypotheses of its pathogenesis centered on the role of inflammatory processes as well as immune infiltration in the microenvironment. However, there are a lot of discrepancies when it comes to the verification of certain well-recognized pathways involved in the dys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…The concept of keloid microenvironment has been frequently evoked to describe the complex cellular and molecular interplay that gives rise to and sustains keloidogenesis. Recent technologies, such as identification of differentially expressed genes via examination of RNA sequencing data sets ( 74 , 75 , 78 80 ), have led to more extensive analysis of keloid tissue. A skewed T helper (Th) 2 phenotype was recently characterized ( 81 85 ), along with a potential co-susceptibility of keloids and atopic dermatitis ( 6 , 12 , 86 ).…”
Section: Introductionmentioning
confidence: 99%
“…The concept of keloid microenvironment has been frequently evoked to describe the complex cellular and molecular interplay that gives rise to and sustains keloidogenesis. Recent technologies, such as identification of differentially expressed genes via examination of RNA sequencing data sets ( 74 , 75 , 78 80 ), have led to more extensive analysis of keloid tissue. A skewed T helper (Th) 2 phenotype was recently characterized ( 81 85 ), along with a potential co-susceptibility of keloids and atopic dermatitis ( 6 , 12 , 86 ).…”
Section: Introductionmentioning
confidence: 99%
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Manipulated or compromised peer review …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%